IMMER LAND INTESTINAL BIOPSY SPECIMENS OF NEWBORNS IN HIGH-FREQUENCY ELECTRIC FIELD SHOW ORIGINAL - V. A. Tarakanov; E. G. Kolesnikov; O. A. Tereshchenko; A. E. Stryukovsky; I. S. Levchenko; N. V. Pelipenko; A. V. Shatov; R. V. Morozova (Кубанский научный медицинский вестник)
In order to determine the amount of resection of the small intestine area child with necrotizing enterocolitis, the parameters of the emission in the high field section of healthy tissue biopsies were studied area with paranecrosis and necrosis of the small intestine. All biopsy specimens obtained edge emission (Kirlian effect). In areas paranecrosis and necrobiosis took place inside the fabric glow. At a later stage of necrosis inner glow disappeared. Brightness, wavelength range in the early stages of necrosis exceed those parameters when paranecrosis. It is the distinctive features in the assessment of small bowel segments.